Amniocentesis is a safe and effective prenatal diagnostic tool: a clinical study in Eastern India - Mukherjee, Kanchan; Chaudhury, Kalyansree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Aim of current study was to estimate the benefits of amniocentesis for diagnosis of fetal chromosomal abnormalities as well as the risk of miscarriage in Indian women and thus provide local data for counselling the prospective parents contemplating amniocentesis. Methods: This retrospective study reviewed the miscarriage rate of 243 pregnant women who underwent midtrimester amniocentesis for prenatal diagnosis of fetal chromosomal abnormalities. 20 ml of amniotic fluid was aspirated under ultrasound guidance. Results: Only three women had miscarriage, two of them within a week of the procedure and the other one after two weeks. The miscarriage rate in this study was 1.23% which was not statistically significantly different from the miscarriage rate found in a large trial, faster trial, taken as reference. Conclusions: Two factors, indications for amniocentesis as well as the procedure itself, contribute to the risk of miscarriage. The procedure-related risk is very low and the total risk of miscarriage is around one percent. Amniocentesis is a safe and effective prenatal diagnostic procedure.